PENGARUH PESAN DAKWAH AKUN INSTAGRAM @HANAN_ATTAKI TERHADAP RELIGIUSITAS PARA FOLLOWERS - Rappedeo, Muhammad Iqbal; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Instagram is a social media where can upload photos, videos and information can be accessed quickly by other people in bulk. Many of the content presented by Instagram users is about da'wah, this is used by the da'i to spread preaching messages to the public such as the @hanan_attaki Instagram account which is now followed by 6.2 million Instagram users. Instagram account @hanan_attaki can help followers get information about religion that can affect their religiosity. Religiosity is a benchmark of a person's religious quality.  This study purpose is to analyze how much the effect of @hanan_attaki Instagram account towards the level of religiosity of its followers.This study uses a quantitative method with an explanatory approach. The data collecting technique uses is by questionnaire distributed through links to 100 respondents. This study uses simple ramdom sampling to determine the sample. Data processing using are done with SPSS 2.0.In this study obtained t count 14.765 is greater than ttable, which is equal to 1.987, with a significance level of 0.000 smaller than α = 0.05, so that it can be stated that the variable X affects the variable Y, it can be stated that there is the influence of da'wah messages on Instagram accounts @hanan_attaki on the level of religiosity of the followers. the coefficient of determination (R2) obtained is 0.8312 and the coefficient of determination (Rsquare) is 0.690 resulting from the squaring of the correlation coefficient 0.831 x 0.831. This figure shows that the influence of the @hanan_attaki Instagram account message on the followers' religiosity level was 69.0% with a strong category.Key Word : Media Social, Instagram, Religiousity, @hanan_attaki, Da’wah Massage